2023
DOI: 10.1186/s12933-023-02000-5
|View full text |Cite
|
Sign up to set email alerts
|

Timing of SGLT2i initiation after acute myocardial infarction

Dirk von Lewinski,
Ewald Kolesnik,
Faisal Aziz
et al.

Abstract: Background Pharmacological post-MI treatment is routinely initiated at intensive/cardiac care units. However, solid evidence for an early start of these therapies is only available for dual platelet therapy and statins, whereas data on beta blockers and RAAS inhibitors are heterogenous and mainly limited to STEMI and heart failure patients. Recently, the EMMY trial provided the first evidence on the beneficial effects of SGLT2 inhibitors (SGLT2i) when initiated early after PCI. In patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The administration of 10 mg Empagliflozin has beneficial cardiac effects including reduction in NTproBNP levels as well as improvements in structural (LVESV and LVEDV) and functional cardiac parameters (LVEF, E/eʹ) compared to placebo after AMI if administered early after PCI 20 . Furthermore, the very early administration of SGLT2-inhibitors appears to have no disadvantages with respect to safety post AMI and was found to be effective in reducing NTproBNP levels and structural as well as functional cardiac parameters 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The administration of 10 mg Empagliflozin has beneficial cardiac effects including reduction in NTproBNP levels as well as improvements in structural (LVESV and LVEDV) and functional cardiac parameters (LVEF, E/eʹ) compared to placebo after AMI if administered early after PCI 20 . Furthermore, the very early administration of SGLT2-inhibitors appears to have no disadvantages with respect to safety post AMI and was found to be effective in reducing NTproBNP levels and structural as well as functional cardiac parameters 22 .…”
Section: Discussionmentioning
confidence: 99%
“…We found a slight improvement of ejection fraction in the only cohort with SGLT‐2i, confirming the potential CV benefit of this class of treatment. Empagliflozin already showed a significant improvement in LVEF in patients undergoing percutaneous coronary intervention for myocardial infarction in the EMMY trial 30 . Furthermore, in a trial of 88 patients with diabetes with heart failure with reduced ejection fraction the use of canagliflozin resulted in a significant improvement in LVEF compared with sitagliptin after 12 weeks 31 …”
Section: Discussionmentioning
confidence: 99%
“…Empagliflozin already showed a significant improvement in LVEF in patients undergoing percutaneous coronary intervention for myocardial infarction in the EMMY trial. 30 Furthermore, in a trial of 88 patients with diabetes with heart failure with reduced ejection fraction the use of canagliflozin resulted in a significant improvement in LVEF compared with sitagliptin after 12 weeks. 31 SGLT-2i showed multiple pleiotropic effects, including antiatherosclerotic effect by reducing vascular inflammation and oxidative stress, improving endothelial dysfunction.…”
Section: Safetymentioning
confidence: 99%
“…Therefore, our findings might be partially outdated, especially as they do not mirror the introduction of sodium-glucose co-transporter 2 inhibitors as guideline-directed medical therapy in HF, and randomized controlled tri-als have shown that these drugs decrease NT-proBNP in both acute and chronic settings. [34][35][36] We lacked information on the use of intravenous diuretic treatment, and we consequently defined a WHFE only according to a hospitalization for HF.…”
Section: Strengths and Limitationsmentioning
confidence: 99%